TOXIC RELATIONSHIPS AMONG FEMALE MUSLIM STUDENTS IN URBAN AREAS - Dinda Adilla; Dwi Amalina Putri; Ayu Diah Nurjunima; Novela; Puan Harum Majid; Zaidi Naufal Al Fayyaadh; Brahua; Azzahra Julia Nadina; Annisa Syifa Azzahrah; Salma Firnanda; Ghina Ulayya; Sonya Damayanti; Aliatunnisa Amanda; Tasya Amelia Sari; Alvin Destian Ronaldi; Fathiya Ar Ghina Khansa (Journal of Islamic Psychology and Behavioral Sciences, 2023)
Toxic relationships are unhealthy and unhappy toxic relationships or relationships that do not support each other. This study is limited, the purpose of this study is to identify and analyze unhealthy relationships in toxic relationships of urban women among adolescents. Especially like college students who are now mostly toxic to the people closest to them. Toxic relationships as unhealthy relationships have an impact on internal conflict. This kind of relationship is very vulnerable to making the sufferer unproductive, mental disorders, making emotional outbursts that lead to violence. Usually this toxic relationship occurs a lot in urban areas, because teenage parents tend to provide poor parenting and lack of affection from their parents. The research method used is a quantitative approach. Data collection techniques using questionnaire surveys, statistical datasets. The results of the study show that: toxic relationship perpetrators are dominated by women, can also be categorized into several forms, namely: unhealthy relationships with friends, family, or lovers / boyfriends.